2020
DOI: 10.3390/cells9030565
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Presenting XCR1+ Dendritic Cells as Targets for Cancer Immunotherapy

Abstract: The use of dendritic cells (DCs) to generate effective anti-tumor T cell immunity has garnered much attention over the last thirty-plus years. Despite this, limited clinical benefit has been demonstrated thus far. There has been a revival of interest in DC-based treatment strategies following the remarkable patient responses observed with novel checkpoint blockade therapies, due to the potential for synergistic treatment. Cross-presenting DCs are recognized for their ability to prime CD8+ T cell responses to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 194 publications
(245 reference statements)
0
31
0
Order By: Relevance
“…Conventional type 1 DCs, which we found to be more abundant in irradiated tumors, are becoming increasingly recognized for their importance to prime and activate CD8+ T cells by the uptake and cross-presentation of tumor antigens [ 54 ]. Direct targeting of those cells or relocating the injection point to a peritumoral injection of the vaccine after irradiation, a point where cDC1s are already present, might additionally improve HHP vaccine efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional type 1 DCs, which we found to be more abundant in irradiated tumors, are becoming increasingly recognized for their importance to prime and activate CD8+ T cells by the uptake and cross-presentation of tumor antigens [ 54 ]. Direct targeting of those cells or relocating the injection point to a peritumoral injection of the vaccine after irradiation, a point where cDC1s are already present, might additionally improve HHP vaccine efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in pre-clinical trials, cDC1s have been shown to be essential for the treatment with ICIs as the treatment efficacy is abrogated in cDC1 deficient Batf3-/- mice [ 52 , 53 ]. As cDC1s express receptors specific for the recognition of dead and dying cells [ 54 ], they might not only be important to initiate CTL responses in irradiated tumors where ICD is induced, but might also be required for the cross-presentation of HHP vaccines and could be targets for further improvements of those vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the chemokine receptor XCR1 is presented as a universal surface marker on cross-presenting DCs ( 161 ) in mice as well as humans. This marker is also present on cDC1 + DCs and, therefore, it is thought that XCRI + DCs are crucial in creating successful adaptive immune responses against viruses ( 162 ). In addition, pDCs, which do not express XCR1, are considered to cross-present in humans ( 144 146 ).…”
Section: Human Dendritic Cell Subsets and Cross-presentationmentioning
confidence: 99%
“…cDCs consist of 2 large groups: cDC type 1 (cDC1) and type 2 (cDC2). cDC1 are key players in the regulation of cancer immune responses due to their ability to cross-present antigens to CD8 + T cells and to generate cytotoxic effector T cell responses (3)(4)(5)(6). Their presence is critically important for the success of immunotherapies, such as adoptive T cell transfer and checkpoint blockade (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%